STUDY ON SATISFACTION LEVEL IMPLEMENTATION OF E-LEARNING AS SUPPORTING MEDIA LEARNING THE ACADEMY AVIATOR INDONESIA BANYUWANGI - Ahmad Hariri; Ahmad Mubarok; Untung Lestari Nur Wibowo; M. Akbar Fathafirza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Good quality education is one key to the progress of civilization and improvement of living standard of a nation. In order to achieve a good quality of education needed an integrated learning process by using different methods of learning and innovation that allows a continuous learning not limited by space and time. Teaching and learning activities between teachers and students with the conventional method through face to face that had been applied to the weakness of the method of learning with face-to- face methods in Indonesian Civil Pilot Academy can be minimized by providing learning facilities online or e-learning which can be accessed by all students at any and anywhere as long as connected to the internet. The scope of the problem under study is how to design and implement e-learning Indonesian Civil Pilot Academy The purpose of this research is the availability of e-learning application of Indonesian Civil Pilot Academy, while the expected benefits of this research is the ease for students in conducting learning activities without time and space is limited, while the objective of this study was teachers and Indonesian Civil Pilot Academy. The method used in this work is the method of library practice, observation, interviews, analysis, design and pilot projects. With the application of e-learning co- produced learning facilities outside learning with face to face methods.